2015
DOI: 10.1155/2015/535938
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 Plasma Concentrations Predict Mortality in HBV‐Related Acute‐on‐Chronic Liver Failure

Abstract: Hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) is a rapidly progressing and frequently fatal condition. The aim of this study was to determine whether interleukin- (IL-) 33 and soluble ST2 (sST2) were associated with disease severity and mortality in HBV-ACLF. We found that plasma levels of sST2 but not IL-33 were higher in HBV-ACLF patients compared with chronic hepatitis B (CHB) patients and healthy controls. However, plasma levels of IL-33, TNF-α, IFN-γ, and IL-10 did not correlate with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 48 publications
9
17
0
Order By: Relevance
“…Results of IHC staining for IL‐33 were similar to the findings of previous reports . IL‐33 staining was concentrated in the nuclei of vascular endothelial cells and sinusoidal endothelial cells in areas of inflammation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Results of IHC staining for IL‐33 were similar to the findings of previous reports . IL‐33 staining was concentrated in the nuclei of vascular endothelial cells and sinusoidal endothelial cells in areas of inflammation.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have concluded that sST2 may be a useful biomarker for cardiovascular disease and inflammation, for example, heart failure and sepsis . In addition, serum sST2 levels predict mortality in HBV‐related acute‐on‐chronic liver failure . In our study, we found the sST2 level to be significantly increased in serum of patients with AIH compared with that of patients with PBC and HCs.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The complement system is an important part of the immune system in humans, and serum levels of complement C3 and C4 serve an important role in human immunity (34). Serum complement C3 and C4 levels have previously been reported to be reduced in patients with HBV (35). In the present study, the serum levels of complement C3 and C4 were significantly higher in the compensated group compared with the decompensated group at the baseline.…”
Section: Discussionsupporting
confidence: 52%
“…Elevated concentrations of this decoy receptor might indicate adverse prognosis in hepatocellular carcinoma. 17,18 Since its discovery in 2005, 4 it has become evident that IL-33 is a versatile cytokine that influences the formation and severity of liver disease. The study by Tan et al emphasizes the crucial role of IL-33 in the formation of liver fibrosis.…”
mentioning
confidence: 99%